PENGARUH NILAI TUKAR, INFLASI DAN PRODUK DOMESTIK BRUTO TERHADAP NERACA TRANSAKSI BERJALAN - Mevia, Sintya Bella Artha (Journal of Financial Economics & Investment, 2021)
In theory, if the exchange rate depreciates and inflation falls, the current account balance will increase. However, the exchange rate in 2012, 2013 and 2018 depreciated and inflation in 2012 and 2018 fell but current transactions also fell. Likewise, inflation in 2017 rose but current transactions also rose. This study uses a quantitative approach using secondary data through Bank Indonesia and the Central Statistics Agency. With the results of sig. The t-statistic test is 0.89 > 0.05 and the t-count value is 1.744 < t table (2,015). This is not in accordance with the hypothesis. The inflation variable has a negative and significant relationship to the current account balance in Indonesia. With the results of the t-statistics test with a negative value of t-count is -3.025 < t table (2.015) with a sign value. of 0.02 < 0.05. The gross domestic product variable has a negative and significant relationship to the current account balance in Indonesia. the results of the t-statistics test with a tcount of -3.231 < t table (2,015) with a sig value. of 0.04 < 0.05. This is in accordance with the hypothesis that the exchange rate has a positive but not significant effect on the current account balance. Inflation and gross domestic product have a negative and significant effect on Indonesia's current account balance.